Ossification of the mamillo-accessory ligament: a review of the literature and clinical considerations - Dupont, Graham (Anat Cell Biol, 2019)
Ossification of the mamillo-accessory ligament (MAL) is a misunderstood phenomenon; however, many have posited that it can result in nerve entrapment of the medial branch of the dorsal ramus causing zygapophyseal joint related low back pain. The MAL has been studied anatomically by few, yet the data indicate possible associations between ossification of this ligament and spondylosis. It has been proposed that mechanical stress upon the lumbar spine may also lead to progressive ossification of the MAL into a bony foramen.